CREAS e a violência doméstica contra crianças e adolescentes: tramas do cotidiano no Vale do Ivaí - Machado, Vanessa Rombola (2020)
This thesis is about the challenges faced in ensuring protection, defense and promotion of children’s and adolescents’ rights in a situation of domestic violence, based on the configuration of actions by the Specialized Social Assistance Reference Center (CREAS). The territorial focus of the research is on Vale do Ivaí region – State of Paraná, comprehending 10 municipalities, concerning the identification of social protection demands and offers related to domestic violence against children and adolescents. The research captured the movement of reality in a perspective of totality, aiming to unveil the root of social phenomena. The research had a quantitative focus by means of data collection from official sources for characterizing the territory, and qualitative focus by means of testimonials from experiences had by 19 workers at CREAS from the 10 municipalities and the Regional Office in Ivaiporã. The data collected demonstrated the ineffectiveness of CREAS technical team, in accordance with the NOB-RH (Basic Operational Rules of Human Resources) precepts, in some municipalities, associated with precarious conditions not only structural in the service, with respect to non-fulfillment of its attributions, and lack of effectiveness of the National Policy of Training and Permanent Education of SUAS (Unified Social Assistance System). It was also made evident the existence of high numbers of violence notifications in municipalities of Small Size I, being physical violence the most frequent one. The perception of violence as a social and historical process was present in the interviewees’ answers, as well as an emphasis on the violence practiced by the State itself, for not ensuring rights. Domestic violence against children and adolescents presented in the state of Paraná, more specifically in the region of Vale do Ivaí, is based on cultural values arising from colonization, with strong sexist and patriarchal marks, and which are expressed by conservative attitudes, by stigmatizing victims and aggressors. It became evident, in the field of public management, that it is necessary to record more information and notification related to children and adolescents victims of violence